Exploring communication strategies in english speaking skills: a study of students at the university of danang, university of foreign language studies - Lưu Ngọc Bảo Thi (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study focuses on communication strategies, specifically examining how they are perceived and used in English speaking activities, as well as the impacts of verbal communications strategies on performances of second-year English students from the Faculty of Foreign Language Teacher Education and the Faculty of English at the University of Danang-University of Foreign Language Studies (hereafter called EFL students for brief) as well as to propose appropriate solutions to assist them to improve their communication skills. Data were collected from 280 questionnaires and the analysis of the in-depth interviews conducted with 10 student participants and observations of 40 students in total. The findings show that most students were familiar with the term “communication strategies”, though they did not know exactly what the term referred to. Additionally, EFL second-years employed all twelve studied VCSs at various frequency. Both positive and negative influences were reported, and judgement about errors from surrounding people was chosen to be the biggest obstacle when applying VCSs. To solve these problems, several solutions were discussed in the study